Cryptic lineages and Pleistocene population expansion in a Brazilian Cerrado frog - Prado, Cynthia P. A. [UNESP]; Haddad, Celio Fernando Baptista [UNESP]; Zamudio, Kelly R. (Wiley-Blackwell, 2012)
Diversification of South American species endemic to open habitats has been attributed to both Tertiary events and Pleistocene climatic fluctuations. Nonetheless, phylogeographical studies of taxa in these regions are few, precluding generalizations about the timing and processes leading to differentiation and speciation. We inferred population structure of Hypsiboas albopunctatus, a frog widely distributed in the Brazilian Cerrado. Three geographically distinct lineages were recovered in our phylogeny. The Chapada dos Guimaraes (CG) clade was the first to diverge from other populations and contains multiple haplotypes from a single population in western Cerrado, probably representing a cryptic species. The southeast clade (SE) includes populations along the southeastern limit of the range within the historical distribution of the Brazilian Atlantic forest. Finally, the Central Cerrado (CC) group includes haplotypes from the interior of Brazil that are paraphyletic relative to the SE clade. Analyses of historical demography indicate significant population expansion in the CC and SE populations, likely associated with colonization of newly formed open habitats. The divergence of populations in the CG clade occurred in the late Miocene, concordant with the uplift of the central Brazilian plateau. Divergence of the SE clade from the CC occurred during the mid-Pleistocene. Thus, both Tertiary geological events and Pleistocene climatic fluctuations promoted divergences among lineages. Our study reveals a complex history of diversification in the Cerrado, a morphoclimatic domain highly threatened because of anthropogenic habitat alteration. We identified surprisingly deep divergences in a widely distributed frog, indicating that the Cerrado is not a barrier-free habitat and that its diversity is likely underestimated.
Keywords: Anura; demographic history; Hylidae; mtDNA; Neotropical savanna; Phylogeography